Chromatographic study of the structural properties of mesoporous silica layers deposited on radially elongated pillars - Futagami, Shunta; Hara, Takeshi; Ottevaere, Heidi; Terryn, Herman; Baron, Gino V.; Desmet, Gert; De Malsche, Wim (Journal of Chromatography A, 2019)
•Layer thickness was altered by adjusting feed composition and gelation temperature.•Mesopore size was controlled by changing HT temperature.•Thicker layer and HT at 80 °C increased retention for small molecules, as expected.•HT at 80 °C provided better performance for MWs of up to 1000.•HT at 105 °C was more advantageous for MWs of larger than 1000. We report on the ability to change the layer properties of porous layered radially elongated pillar (PLREP) array columns and its relevance to the separation efficiency. The adjustment of the preparation condition resulted in the formation of a 1.2-fold thicker layer than the layer produced in the preceding study. The mesoporosity of the layer was controlled by changing the hydrothermal treatment temperature from 105 °C to 80 °C. Chromatographic characterization was performed on a commercial nano-LC system using the octadecylsilylated PLREP columns having the aforementioned characteristics, i.e. (1) different layer thickness (df = 180–220 nm) and (2) different mesoporosity (dp = 7.6–11.2 nm, Pore volume (Vp) = 0.733‒0.838 cc/g and Surface area (SA) = 364‒611 m2/g). For isocratic separations of an alkylphenone mixture, the change in both the layer thickness and the mesoporosity caused no significant difference in the column efficiency, while the thicker layer and the reduction of mesopore size resulted in a 1.3-fold increase and a 1.4-fold increase in the retention capacity, respectively. Based on the result of the examination using scanning electron microscopy and argon physisorption technique, the formar enhancement was in agreement with the increase in the layer thickness, and the latter one was attributed to the larger surface area. When applying a column with 16.5 cm long to gradient separations, the combination of the thicker layer and the smaller mesopores provided the peak capacity of 365 for the alkylphenone mixture at a 180 min gradient, while the combination of the thinner layer and the larger mesopores provided the peak capacity of 315. For peptide separations, it appeared that the thicker layer was still favorable, however, the lager mesopores were more advantageous for MWs of larger than 1000, providing a conditional peak capacity of 245 for a commercially available peptide mixture because of less content of small pores which hinder the diffusion of large molecules in pores in the layer.